Talaşlı imalatta iş değerlemesi ve yeni faktörlerin incelenmesi - Yüce, Hakan (My University, 2009)
THE JOB EVALUATION OF THE MACHINING AND INVESTIGATION OF THE NEW FACTORS Job Evaluation aims the fair distribution of wages to the employees. Job Evaluation evaluates the work, not the worker. Job Evaluation, which has been hitherto used but occasionally suspended on account of the fact that it is inefficient, is quite an important method with respect to its justice and preventing undeserved gain. It was seen in the research projects that there is a lack of study on the factors which were determined by the survey applied in this study dealing with machining in Turkey, although it has been practiced in recent years and new methods have been developed for it. In the Job Evaluation study carried out by Turkey Metal Industry Syndicate (MESS), the usage of the factors which have lately gained significance and which have been excluded from Job Evaluation was taken into account. In addition, effects, applications and descriptions of the specified factors were analyzed. For specifying the factors, surveys were carried out in Bursa and Istanbul regions, and the data was processed with Pareto analysis. Analytical Hierarchy Process was chosen as the Job Evaluation method in this study, due to the fact that it is practical and it provides an opportunity of working systematically, by removing any subjective judgment. By using scoring method, a comparison was made between Analytical Hierarchy Process and the results of Job Evaluation applied. Additionally, this study covers a detailed description of Analytical Hierarchy Process. In spite of the fact that Analytical Hierarchy Process has been practiced in Job Evaluation, it has been presented as an applicable Job Evaluation study, as the method is a special study which not only deals with machining, but also evaluates the specified factors and sub-factors. Also, in this study mentioned of waging, the wage curves have been drawn by using job evaluation results and new factors are presented.

TALAŞLI İMALATTA İŞ DEĞERLEMESİ VE YENİ FAKTÖRLERİN İNCELENMESİ İş Değerleme, ücretlerin çalışanlara adil bir şekilde dağıtılmasını hedeflemektedir. İş değerleme işi değerlendirir, çalışanı değil. Günümüze kadar uygulanan, zaman zaman verimli olmadığı düşünülerek uygulamasına ara verilen iş değerleme, özünde adaleti ve haksız kazançların önüne geçmesi bakımından oldukça önemli bir yöntemdir. Son yıllarda uygulanan ve üzerinde yeni yöntemler geliştirilmesine karşın, Türkiye’de talaşlı imalata özel bu çalışmada uygulanan anket ile belirlenen faktörlerin üzerinde çalışılmamış olduğu yapılan araştırmalarda görülmüştür. Türkiye Metal Sanayi Sendikacıları (MESS) ‘ in yaptığı iş değerleme çalışmasında son zamanlarda önemi artan ve iş değerlemesine katılmayan faktörlerin kullanımı, bu çalışmada göz önüne alınmıştır. Ayrıca belirlenen faktörlerin etkileri uygulamaları ve tanımlamaları incelenmiştir. Faktörler belirlenirken Bursa ve İstanbul yöresinde anket çalışması uygulanmış ve Pareto analizi ile eliminasyonu yapılmıştır. Bu çalışmada uygulanan İş değerleme yöntemi, uygulamada kolaylık sağladığı için, subjektif yargıları ortadan kaldırarak ve sistematik bir çalışma sağladığından dolayı Analitik Hiyerarşi Süreci seçilmiştir. Puanlama yöntemi kullanılarak, Analitik Hiyerarşi süreci yöntemi ile uygulanan iş değerleme sonuçları arasında karşılaştırma yapılmıştır. Analitik Hiyerarşi Sürecinin daha önce iş değerlemesinde uygulaması olmasına rağmen, yöntem talaşlı imalatı ele alan ve belirlenen faktör ve alt faktörleri de değerlendiren özel bir çalışma olduğu için uygulanabilir bir iş değerleme çalışması olarak sunulmuştur. Ayrıca Ücretleme konusuna değinilen bu çalışmada iş değerleme sonuçları kullanılarak ücret eğrileri çizilmiştir ve yeni faktörlerin incelenmesi sunulmuştur.
Keywords: İş Değerleme; Talaşlı İmalatta